2012
DOI: 10.3389/fnagi.2012.00003
|View full text |Cite
|
Sign up to set email alerts
|

Differences between Old and Young Adults’ Ability to Recognize Human Faces Underlie Processing of Horizontal Information

Abstract: Recent psychophysical research supports the notion that horizontal information of a face is primarily important for facial identity processes. Even though this has been demonstrated to be valid for young adults, the concept of horizontal information as primary informative source has not yet been applied to older adults’ ability to correctly identify faces. In the current paper, the role different filtering methods might play in an identity processing task is examined for young and old adults, both taken from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 51 publications
2
27
1
Order By: Relevance
“…When recognizing unfiltered faces exposure duration and stimulus age had equal effects on both age groups. This finding adds to the notion that YA and OA do indeed process horizontal information differently (Obermeyer et al, 2012). …”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…When recognizing unfiltered faces exposure duration and stimulus age had equal effects on both age groups. This finding adds to the notion that YA and OA do indeed process horizontal information differently (Obermeyer et al, 2012). …”
Section: Discussionsupporting
confidence: 69%
“…The present study was conducted to extend the research reported by Obermeyer et al (2012). First, only young faces were presented to both age groups.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations